EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK PENGENDALIAN DIRI MENGURANGI INTENSITAS PENGGUNAAN PERMAINAN DALAM JARINGAN - ISTI FAHRURROZI MUHAMMAD ILHAM (Jurnal Psikoedukasia, 2023)
The background of this study is low self-control, lack of focus on learning, often absent from learning due to excessive playing games. Problems (1) how is the process of self-control techniques for group guidance services to reduce the intensity of using online games, the impact of implementing group guidance services. This type of research is pre-experimental designs (non-design) experiments that are not real. Pre-experimental design method type one group pretest-posttest. This research was conducted at SMPN 2 Pegandon, Ngampel District, Kendal Regency. purposive sample taking, 8 students of class VIII F. data collection, observation, interviews, questionnaires, and documentation. Data analysis; descriptive, and statistical analysis. Results (1) Group guidance services using self-control techniques were carried out in class VIIIF for three meetings. Service procedures include introductory, core, and closing activities, (2) after being treated with group guidance services with self-control techniques for students, the majority of students or 66.7% are incapacitated by an individual in controlling the use of the internet or video games in the light category network